Propagação vegetativa de Selenicereus setaceus e a influência da temperatura e luminosidade na germinação das espécies Selenicereus setaceus, Hylocereus undatus e Hylocereus polyrhisus - Ruths, Rodrigo (2016)
The fruit is great potential for diversification into agro-ecological ecosystems and pitaya is a fruit with great productive potential, nutritional, economic and social to family farming, and even little-known culture and with little information. The objective of this study was to obtain information about the influence of temperature and light on germination of three species of dragon fruit: Selenicereus setaceus (pitaya-do-cerrado), Hylocereus undatus (red skin and white flesh) and Hylocereus polyrhizus (pinkish red bark and red pulp); and what the best segments of cladodes and treatments for seedling production of the species S. setaceus. For the evaluation of the physiological quality of seeds were carried out the following evaluations: moisture content, germination percentage, germination speed index and time to occurrence of 50% germination. For vegetative propagation, the experiment was conducted in a factorial 5x4x7, 5 treatments: one biofertilizers (fertile fish - Classic), three plant growth regulators, auxin (IAA: 500 ppm), gibberellic acid (GA 3: 100 ppm), cytokinin (BAP: 200 ppm) and witness. Four fractions cladodes apical segment (10 cm), medium segment (10 cm), basal segment (10 cm) and full cladodes (40 cm), and seven periods of evaluation, 0, 20, 39, 64, 91, 116 and 143 days after planting. We used a completely randomized design with three replications and plots were composed of five cladodes. The following parameters were evaluated: number of shoots, length of shoots (cm); cladodes width (cm); root length (cm), root dry weight (g) and percentage of rooted cladodes. From the results obtained it is concluded that: Regardless of species, the temperature for best physiological performance of dragon fruit seeds is 25° C, followed by 30°C. Moreover, the unfavorable temperature is 35°C. The species Selenicereus setaceus has a higher percentage of germination and vigor in all tested temperatures. All assessed species are photoblastic positive. The cladodes treated with auxin have higher average root length and dry weight, while those treated with lower biofertilizers. The dry weight of whole cladodes root is higher than that observed for cladodes 10 cm. From 39 days after the implementation of the experiment, the treatments with whole cladodes and basal region have higher average number of shoots compared the median and apical regions. Treatments with auxin and cytokinin promote more shoots in cladodes. The greatest length of shoots is observed for treatment with whole cladodes.